2020
DOI: 10.3390/ijms21249767
|View full text |Cite
|
Sign up to set email alerts
|

Chlorinated Guaiane-Type Sesquiterpene Lactones as Cytotoxic Agents against Human Tumor Cells

Abstract: Guaiane-type sesquiterpene lactones are naturally occurring compounds which have attracted attention due to their array of biological activities. In this study, chlorinated guaianolides 1–8, isolated from plants of the genus Centaurea, were evaluated against the human leukemia cell lines HL-60, U-937, a specific U-937 cell line that overexpresses the anti-apoptotic Bcl-2 protein and the human melanoma cell line SK-MEL-1. This established the relevant structure-growth inhibition relationships. Chlorohyssopifoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
(43 reference statements)
2
4
0
Order By: Relevance
“…The effects of guaiane‐type sesquiterpene lactones from genus Centaurea were evaluated against the human leukemia cell lines. Chlorohyssopifolins A, C, and D and linichlorin A showed an IC50 of about 10 μM in all cell lines [60] . In summary, the compounds studied in the current research showed a lower cytotoxic effect in comparison with similar compounds evaluated in the previous study.…”
Section: Resultssupporting
confidence: 48%
See 1 more Smart Citation
“…The effects of guaiane‐type sesquiterpene lactones from genus Centaurea were evaluated against the human leukemia cell lines. Chlorohyssopifolins A, C, and D and linichlorin A showed an IC50 of about 10 μM in all cell lines [60] . In summary, the compounds studied in the current research showed a lower cytotoxic effect in comparison with similar compounds evaluated in the previous study.…”
Section: Resultssupporting
confidence: 48%
“…Chlorohyssopifolins A, C, and D and linichlorin A showed an IC50 of about 10 μM in all cell lines. [60] In summary, the compounds studied in the current research showed a lower cytotoxic effect in comparison with similar compounds evaluated in the previous study. Between these two compounds, compound 2 is more cytotoxic than compound 1 and exhibited a lower toxic effect on normal cells.…”
Section: Cytotoxicity Activitysupporting
confidence: 57%
“…To obtain an analogue of chlorine-containing biologically active guaianolides [ 20 , 21 , 22 , 23 ], we studied the interaction of estafiatin 1 with a solution of hydrogen chloride in methanol. This formed a mixture of two substances with R f 0.55 and 0.45.…”
Section: Resultsmentioning
confidence: 99%
“…3.4 µM and 3.6 µM (72 h), respectively. Of note, chlorohyssopifolin C and D also showed IC 50 values below 10 µM [108].…”
Section: Other Sesquiterpenoidsmentioning
confidence: 94%